Familial Mediterranean fever gene mutations as a risk factor for early coronary artery disease. (7th April 2014) - Basar, Nurcan; Kisacik, Bunyamin; Ercan, Suleyman; Pehlivan, Yavuz; Yilmaz, Sedat; Simsek, Ismail; Erdem, Hakan; Ozer, Orhan; Pay, Salih; Onat, Ahmet M.; Dinc, Ayhan
Abstract: Objective: Cardiovascular diseases (CVD) are very common in the general population. Atherosclerosis is the main pathogenesis. Familial Mediterranean fever (FMF) is an autosomal recessive disease. The gene causing FMF, designated MEFV, encodes a protein called pyrin or marenostrin that is expressed mainly in myeloid bone marrow precursors, neutrophils and monocytes. We herein aimed to determine the prevalence of MEFV mutations (all exon 2, 10 mutations) in patients with early coronary heart disease (early CHD) and coronary heart disease (CHD) with multiple risk factors and among the healthy subjects as controls. Methods: A total of 197 patients and 119 healthy subjects were recruited and enrolled into three groups in terms of inclusion criteria. Ninety‐one patients diagnosed with early CHD enrolled into group one (men < 45 years of age, women < 40 years of age), 106 patients with CHD (men > 50 years of age) to group two and 119 healthy controls enrolled into group three. None of patients was diagnosed with FMF. The diagnosis of CHD was established on electrocardiographic changes, echocardiography and coronary angiography. Results: Thirty‐eight patients (41.8%) with early CHD, 17 patients (16%) with CHD and 24 healthy controls (20.2%) carried at least one mutated MEFV allele. Young patients with CHD have different risk factor profiles, clinical presentations and prognoses than older patients. Young patients with CHD usually have multiple risk factors. Conclusion: This study suggests that MEFV mutations in early CHD patients had significantly increased in contrast to CHD patients and healthy controls.